Determinants of Financial Distress: The Role of Liquidity, Profitability, Leverage, Sales Growth, and Firm Size in Energy Sector Companies Listed on the Indonesia Stock Exchange for the 2020–2024 Period - Najwa Salsabila Az Zahra; Farida Titik Kristanti (LP2M IAIN Palopo, 2026)
Financial distress has become an important concern because it threatens corporate sustainability, financial performance, and investor confidence. Previous studies have reported inconsistent findings regarding the effects of liquidity, profitability, leverage, sales growth, and firm size on financial distress, particularly in Indonesia's energy sector. Therefore, this study aims to examine the influence of these factors on financial distress among energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This study employs a quantitative approach using secondary data obtained from annual financial statements. The population consists of 89 energy sector companies listed on the IDX, from which 60 companies were selected using purposive sampling, resulting in 300 firm-year observations. Financial distress is measured using the Altman Z-Score model, while panel data regression analysis is employed using EViews 13, with the Common Effect Model (CEM) identified as the most appropriate estimation model. The findings indicate that liquidity, measured by the Current Ratio, has a positive and statistically significant effect on the Altman Z-Score, indicating that stronger liquidity reduces the likelihood of financial distress. In contrast, profitability, leverage, sales growth, and firm size do not exhibit statistically significant effects. These findings suggest that liquidity is the primary financial indicator in maintaining financial stability among Indonesian energy sector companies. This study contributes to the financial distress literature by providing updated empirical evidence from the Indonesian energy sector and offers practical insights for managers, investors, and other stakeholders in assessing corporate financial health and mitigating financial distress risk